2018
DOI: 10.1264/jsme2.me18043
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus-mineralizing Communities Reflect Nutrient-Rich Characteristics in Japanese Arable Andisols

Abstract: Elucidating the soil phosphorus cycle driven by soil microbes is a vital question in soil microbial ecology. The Japanese arable Andisols, occupying half of the Japanese cropland, are known for their high phosphorus sorption capacity. However, limited information is currently available on microbially driven phosphorus mineralization in arable Andisols. We herein report that the phosphorus-mineralizing community in the Japanese arable Andisols showed characteristic distribution and composition patterns, from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…After having corrected for copy number, Piphillin uses direct nearest-neighbor matching of 16S rRNA gene amplicons with genomes from reference databases (e.g., Kyoto Encyclopedia of Genes and Genomes (KEGG), BioCyc) to predict metagenomic content. Piphillin has been broadly used by more than 350 researchers worldwide to study a wide array of microbial environments: including skin [5] and soil microbiomes [6]. Piphillin has distinct advantages over competing tools: Piphillin does not rely on phylogenetic trees to infer metagenomic data and is amenable to frequent database changes (having been updated with six new databases since its inception).…”
Section: Introductionmentioning
confidence: 99%
“…After having corrected for copy number, Piphillin uses direct nearest-neighbor matching of 16S rRNA gene amplicons with genomes from reference databases (e.g., Kyoto Encyclopedia of Genes and Genomes (KEGG), BioCyc) to predict metagenomic content. Piphillin has been broadly used by more than 350 researchers worldwide to study a wide array of microbial environments: including skin [5] and soil microbiomes [6]. Piphillin has distinct advantages over competing tools: Piphillin does not rely on phylogenetic trees to infer metagenomic data and is amenable to frequent database changes (having been updated with six new databases since its inception).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several 16S rRNA gene studies have extended our ability to infer the functional contribution of individual bacterial community members by mapping a subset of abundant 16S rRNA sequences to their nearest sequenced reference genome [12][13][14]. Currently, predicting microbial functions from 16S rRNA gene sequencing data is a common alternative to shotgun metagenomic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that phoD-harbouring bacteria were more influenced by ecosystem restoration practices than apr-harbouring bacteria, with a pronounced decrease in the biodiversity of phoDharboring bacteria with soil development paralleling the processes of passive and active restoration. Previous work has demonstrated that long-term fertilization distinctly increased the microdiversity of phoD-harbouring bacteria (Fraser, Lynch, Bent, et al, 2015;Mise, Fujita, Kunito, Senoo, & Otsuka, 2018;Tan et al, 2013). Meanwhile, the abandonment of farmland can adequately reduce soil N and P concentrations because of the cessation of input from phosphorus-containing fertilizers (Nadal-Romero et al, 2016).…”
Section: Evolution Patterns In Aprand Phodharbouring Bacteria As Ecmentioning
confidence: 99%